A nickel intercalated niobium disulfide

CN122878142APending Publication Date: 2026-10-09HENAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611050887.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0004]为了解决反铁磁性材料产品纯度低、性能较差,制备流程复杂的问题,本发明提供一种镍插层二硫化铌,该反铁磁性材料具有产品纯度高、性能优异、制备流程简便的特点;为了获得上述材料,本发明的技术方案具体如下:

Benefits of technology

[0005]本发明的有益效果:将镍、铌和硫的原材料按照一定比例混合均匀,通过压坯装配在高压合成组装体内,在六面顶压机合成腔内,一定高压和高温完成反应制备得到镍插层二硫化铌;该镍插层二硫化铌具有层状结构,物相均一、产品纯度高、性能稳定等特点;制备过程仅包括原材材料的预处理、坯料的制备,高温高压反应过程,制备流程简便,生产效率高;解决了传统的CVT法插层效率低,反应条件严苛的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878142A_ABST
    Figure CN122878142A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of nickel intercalation niobium disulfide, the nickel intercalation niobium disulfide has layered structure, phase is uniform;The nickel intercalation niobium disulfide belongs to hexagonal system, space group is P6322;Antiferromagnetic phase transition occurs at TN≈55.8 K, temperature is lower than TN, show antiferromagnetic order state;Its preparation steps are as follows: raw material selection and pretreatment: raw material is nickel, niobium and sulfur, according to mole proportion, nickel: niobium: sulfur=1: (2.7-3.2): (5.8-6.1), selected raw material is mixed evenly;The preparation of blank: the raw material mixed evenly in step 1 is placed into mould, and is pre-pressed under the condition of 550-650 MPa to obtain pre-pressed cylinder, obtain blank;And the blank is completed in high-pressure synthesis assembly assembly;Preparation nickel intercalation niobium disulfide: the high-pressure synthesis assembly assembly of blank assembly in step 2 is placed into six-face top press synthesis cavity, and is synthesized under the condition of 2.5-5 GPa, 1300-1650 DEG C for 20-130 min;Synthesis reaction is completed, and temperature is lowered to release pressure, obtain nickel intercalation niobium disulfide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of antiferromagnetic materials technology, specifically to a nickel-intercalated niobium disulfide. Background Technology

[0002] Magnetic intercalated transition metal dichalcogenides (TMDs) have attracted increasing attention in recent years due to their unique electromagnetic behavior, showing broad application prospects in magnetic storage and semiconductor electronics. The structural characteristic of these materials is the insertion of magnetic atoms (such as Fe, Co, and Mn) into the van der Waals interstices of the layered structure of transition metal dichalcogenides. As the amount of insertion increases, the symmetry of the compound increases, while the number of layers gradually decreases. Studies have confirmed that the magnetic properties of magnetic intercalated transition metal dichalcogenides are closely related to the types of intercalated atoms. Taking the NbS2 intercalation system as an example, some intercalated compounds exhibit paraferromagnetism, such as V, Cr, and Mn, while others exhibit antiferromagnetism, such as Co.

[0003] Currently, the traditional preparation method is chemical vapor transport (CVT), which can achieve uniform intercalation of magnetic atoms and chalcogenides without easily disrupting the internal structure. However, CVT has stringent requirements for reaction conditions, typically requiring high-temperature vacuum environments, and also involves long reaction times and low intercalation efficiency. There is an urgent need in the fields of magnetic storage and semiconductor electronics to develop an antiferromagnetic material with high purity, excellent performance, and a simple preparation process. Summary of the Invention

[0004] To address the problems of low purity, poor performance, and complex preparation processes in antiferromagnetic materials, this invention provides a nickel-intercalated niobium disulfide antiferromagnetic material characterized by high purity, excellent performance, and a simple preparation process. The specific technical solution of this invention for obtaining the above material is as follows: A nickel-intercalated niobium disulfide is disclosed, wherein the nickel-intercalated niobium disulfide has a layered structure and a homogeneous phase; the nickel-intercalated niobium disulfide belongs to the hexagonal crystal system with space group P6322; the nickel-intercalated niobium disulfide undergoes an antiferromagnetic phase transition at TN≈55.8 K, and exhibits an antiferromagnetic ordered state at temperatures below TN; the preparation steps of the nickel-intercalated niobium disulfide are as follows: Step 1: Raw material selection and pretreatment: The raw materials are nickel, niobium and sulfur, in a molar ratio of nickel:niobium:sulfur = 1:(2.7-3.2):(5.8-6.1). Mix the selected raw materials evenly. Step 2: Preparation of billet: The raw materials mixed evenly in Step 1 are placed into a mold and pre-pressed under 550-650 MPa to obtain a pre-pressed cylinder, thus obtaining the billet; and the billet is then assembled in a high-pressure composite assembly. Step 3: Preparation of nickel-intercalated niobium disulfide: The high-pressure synthesis assembly of the assembled billet in Step 2 is placed into the synthesis chamber of a six-sided top press and the synthesis reaction is carried out at 2.5-5 GPa and 1300-1650 ℃ for 20-130 min; after the synthesis reaction is completed, the temperature is reduced and the pressure is released to obtain nickel-intercalated niobium disulfide.

[0005] The beneficial effects of this invention are as follows: Nickel-intercalated niobium disulfide is prepared by uniformly mixing raw materials of nickel, niobium, and sulfur in a certain proportion, assembling the raw material into a high-pressure synthesis assembly body through pressing, and completing the reaction under certain high pressure and high temperature in the synthesis chamber of a six-sided top press. This nickel-intercalated niobium disulfide has a layered structure, uniform phase, high product purity, and stable performance. The preparation process only includes the pretreatment of raw materials, preparation of the raw material, and high-temperature and high-pressure reaction process, which is simple and efficient. It solves the problems of low intercalation efficiency and harsh reaction conditions of the traditional CVT method.

[0006] Furthermore, in step 1, the raw materials nickel is metallic nickel, niobium is metallic niobium, and sulfur is elemental sulfur. The uniform mixing specifically refers to uniform grinding, and the grinding and mixing time is controlled within 1 to 3 hours.

[0007] Beneficial effects: The raw materials are selected from metallic nickel, metallic niobium and elemental sulfur, with low impurity content, which is conducive to obtaining products with higher purity. Grinding during the mixing process further improves the uniformity of the mixture.

[0008] Furthermore, the particle size of metallic nickel, metallic niobium, and elemental sulfur in step 1 is 3-300 μm.

[0009] Beneficial effects: Controlling the particle size of raw materials within 3-300μm helps improve the uniformity of the blank material prepared after mixing and grinding.

[0010] Furthermore, the uniform grinding in step 1 is low-temperature grinding, with a grinding temperature below 60°C.

[0011] Beneficial effects: Low-temperature grinding avoids oxidation of raw materials such as nickel, niobium and elemental sulfur during the grinding process.

[0012] Further: In step 2, the assembly process of the billet in the high-pressure synthesis assembly is as follows: a dolomite ring is placed in the central hole of the pyrophyllite synthesis block as a heat insulation layer, and an alumina ceramic tube and a magnesium oxide liner are sequentially inserted into the hole to form an insulation and shaping structure; then a graphite tube is placed as a heating element, and graphite sheets are placed at both ends to form a uniform heating field; next, the sample is encapsulated in a BN sample chamber, and molybdenum sheets and steel sheets are sequentially assembled outside the chamber, and the whole assembly is placed in the center of the magnesium oxide liner; a thermocouple is led out from the sample chamber for temperature monitoring; steel caps are installed at both ends of the synthesis block as electrodes and pressure transmission components, thus completing the preparation of the high-pressure synthesis assembly.

[0013] Beneficial effects: Pyrophyllite, as an excellent pressure-transferring medium, enables uniform pressure transmission during the synthesis process. Simultaneously, it forms a dense layer at high temperatures, providing a stable high-pressure environment for the reaction. Graphite exhibits good electrical conductivity in the direction parallel to the layer; upon energization, the graphite tube heats up, providing the necessary high temperature for the reaction. Furthermore, pyrophyllite possesses excellent thermal insulation properties, ensuring the smooth progress of the reaction at high temperatures. Compared to the traditional CVT method, the high-temperature, high-pressure synthesis method of this invention yields samples with higher purity, fewer impurities, and lower raw material porosity. This method also offers advantages such as easy control of synthesis conditions (temperature, pressure, etc.), low cost, and high efficiency. Attached Figure Description

[0014] Figure 1 This is a SEM image of NiNb3S6 obtained in Example 1 of this invention; Figure 2 The image shows the XRD pattern of NiNb3S6 obtained in Example 1 of this invention. Figure 3 The Raman spectrum of NiNb3S6 obtained in Example 1 of this invention; Figure 4 The graph shows the change in magnetic susceptibility of NiNb3S6 prepared in Example 1 of this invention as a function of temperature. Figure 5 This is a cross-sectional structural diagram of the high-pressure synthetic assembly in this invention; 1-Dolomite ring, 2-Pyrophyllite composite block, 3-Alumina ceramic tube, 4-Magnesium oxide liner, 5-Molybdenum sheet, 6-Steel cap, 7-Steel sheet, 8-BN sample chamber, 9-Sample, 10-Thermocouple, 11-Graphite tube, 12-Graphite sheet. Detailed Implementation

[0015] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments: An embodiment of the present invention, wherein the nickel-intercalated niobium disulfide has a layered structure and a homogeneous phase; the nickel-intercalated niobium disulfide belongs to the hexagonal crystal system with space group P6322; the nickel-intercalated niobium disulfide undergoes an antiferromagnetic phase transition at TN≈55.8 K, and exhibits an antiferromagnetic ordered state at temperatures below TN.

[0016] The preparation steps for this nickel-intercalated niobium disulfide are as follows: Step 1: Raw material selection and pretreatment: The raw materials are nickel, niobium and sulfur, in a molar ratio of nickel:niobium:sulfur = 1:(2.7-3.2):(5.8-6.1). Mix the raw materials evenly.

[0017] In this embodiment, the raw materials are metallic nickel, metallic niobium, and elemental sulfur, with a molar ratio of metallic nickel:metallic niobium:elemental sulfur of 1:3:6. The particle size of metallic nickel, metallic niobium, and elemental sulfur is 100-200 μm. The mixing of metallic nickel, metallic niobium, and elemental sulfur is uniform grinding, with a grinding and mixing time of 2.5 h, to obtain a mixed powder. In other embodiments, the raw materials are metallic nickel, metallic niobium, and elemental sulfur, with a ratio of any value between metallic nickel, metallic niobium, and elemental sulfur of 1:(2.7-3.2):(5.8-6.1). Provided that the particle size of metallic nickel, metallic niobium, and elemental sulfur meets the requirements, uniform stirring can be used instead of uniform grinding. Alternatively, when uniform grinding is used, the uniform grinding time is 1 h or 3 h, with the uniform grinding time determined based on the particle size of the obtained mixed powder.

[0018] In this embodiment, uniform grinding is performed at a low temperature, with the grinding temperature below 60°C, to prevent excessively high temperatures and avoid oxidation of the raw materials, such as nickel, niobium, and elemental sulfur, during the grinding process.

[0019] Step 2: Preparation of the billet: The uniformly mixed raw materials from Step 1 are placed into a mold and pre-pressed at 550-650 MPa to obtain a pre-pressed cylinder, thus obtaining the billet; the billet is then assembled in a high-pressure composite assembly. In this embodiment, the pre-pressing pressure is specifically 620 MPa; in other embodiments, 550 or 650 MPa can be used instead of 620 MPa.

[0020] Step 3: Preparation of nickel-intercalated niobium disulfide: The high-pressure synthesis assembly of the preforms from Step 2 is placed into the synthesis chamber of a six-sided top press and the synthesis reaction is carried out at 2.5-5 GPa and 1300-1650 °C for 20-130 min. After the synthesis reaction is completed, the pressure is released by cooling to obtain nickel-intercalated niobium disulfide. In this embodiment, the six-sided top press is specifically used to carry out the synthesis reaction at 1300 °C and 2.5 GPa for 80 min to complete the synthesis. In other examples, the pressure can be replaced by 3 GPa or 5 GPa instead of 2.5 GPa; the reaction temperature can be replaced by 1400 °C or 1650 °C instead of 1300 °C; and the reaction time can be replaced by 130 min or 20 min instead of 80 min.

[0021] The assembly process of the billet in the high-pressure composite assembly in step 2 is as follows: Figure 5As shown, a dolomite ring 1 is placed in the central hole of the pyrophyllite synthesis block 2 as an insulation layer. Alumina ceramic tube 3 and magnesium oxide liner 4 are then inserted into the hole to form an insulation and shaping structure. Graphite tube 11 is then placed as a heating element, and graphite sheets 12 are placed at both ends to form a uniform heating field. Next, sample 9 is encapsulated in BN sample chamber 8, and molybdenum sheet 5 and steel sheet 7 are assembled on the outside of the chamber. The entire assembly is then placed in the center of magnesium oxide liner 4. Thermocouple 10 is led out from sample chamber 8 for temperature monitoring. Steel caps 6 are installed at both ends of the synthesis block as electrodes and pressure transmission components, thus completing the preparation of the high-pressure synthesis assembly.

[0022] The samples prepared in this embodiment were subjected to SEM, XRD, Raman spectroscopy, and magnetic susceptibility tests.

[0023] from Figure 1 SEM results show that the NiNb3S6 sample prepared in this embodiment has a two-dimensional layered structure with a smooth and uniform surface without obvious defects. The intercalated element Ni is evenly distributed between the layers, and the Ni, Nb, and S distribution ratio is approximately 1:3:6, which is basically consistent with the stoichiometry of the target sample. This proves that the raw materials reacted completely and the element intercalation effect was good. Analysis Figure 2 The XRD results showed five characteristic peaks in the sample: (002), (004), (006), (008), and (0010). These peaks were sharp, and comparison with the standard card confirmed that it was NiNb3S6, with no impurity peaks. This indicates that the magnetic intercalated transition metal chalcogenide NiNb3S6 prepared in Example 1 has high purity, the sample is single-phase, and the technical solution of this example is reasonable and feasible. Figure 3 The Raman spectroscopy analysis results show that single-crystal NiNb3S6 has a sharp Raman peak at around 175 cm-1, indicating that the Ni intercalation effect in Example 1 is good. Figure 3 The illustration shows four vibrational modes of NiNb3S6 at room temperature, including A1g, E1g, E12g, and E22g. Figure 4The magnetic susceptibility test yielded two curves, ZFC and FC. The ZFC (zero-field cooling) curve measures the change in magnetic susceptibility with temperature after cooling the sample to the target low temperature under zero external magnetic field conditions, applying a small measuring magnetic field, and measuring the change during the heating process. The FC (field cooling) curve measures the change in magnetic susceptibility with temperature after cooling the sample under a constant external magnetic field and maintaining that magnetic field while heating. The magnetic susceptibility test results show that above 55.8 K, the two curves almost overlap, indicating that NiNb3S6 exhibits paramagnetism in this state. Below 55.8 K, the two curves bifurcate, indicating that NiNb3S6 undergoes an antiferromagnetic transition at this temperature, exhibiting antiferromagnetism. This demonstrates that the sample prepared by the technical solution of this invention possesses excellent characteristics such as high purity, few defects, and good element intercalation effect, and exhibits antiferromagnetism at a certain temperature. This characteristic determines its important position and potential application value in the field of spintronics.

[0024] The scope of protection of this invention is not limited to the preferred embodiments described above. Without departing from the spirit and core scope of this invention, those skilled in the art can make any modifications or substitutions to the technical solutions, and all equivalent technical solutions should fall within the protection scope of this invention. Furthermore, the temperature, pressure, time, and other synthetic conditions listed in this invention can achieve the purpose of this invention by taking any value within their defined upper and lower ranges; therefore, specific embodiments will not be listed individually here.

Claims

1. A nickel-intercalated niobium disulfide, characterized in that, The nickel-intercalated niobium disulfide has a layered structure and a homogeneous phase; the nickel-intercalated niobium disulfide belongs to the hexagonal crystal system with space group P6322; the nickel-intercalated niobium disulfide undergoes an antiferromagnetic phase transition at TN≈55.8 K, and exhibits an antiferromagnetic ordered state at temperatures below TN; the preparation steps of the nickel-intercalated niobium disulfide are as follows: Step 1: Raw material selection and pretreatment: The raw materials are nickel, niobium and sulfur, in a molar ratio of nickel:niobium:sulfur = 1:(2.7-3.2):(5.8-6.1). Mix the selected raw materials evenly. Step 2: Preparation of billet: The raw materials mixed evenly in Step 1 are placed into a mold and pre-pressed under 550-650 MPa to obtain a pre-pressed cylinder, thus obtaining the billet; and the billet is then assembled in a high-pressure composite assembly. Step 3: Preparation of nickel-intercalated niobium disulfide: The high-pressure synthesis assembly of the assembled billet in Step 2 is placed into the synthesis chamber of a six-sided top press and the synthesis reaction is carried out at 2.5-5 GPa and 1300-1650 ℃ for 20-130 min; after the synthesis reaction is completed, the temperature is reduced and the pressure is released to obtain nickel-intercalated niobium disulfide.

2. The nickel-intercalated niobium disulfide according to claim 1, characterized in that, In step 1, the raw materials are nickel (metallic nickel), niobium (metallic niobium), and sulfur (elemental sulfur). The mixture is uniformly ground, and the grinding and mixing time is controlled between 1 and 3 hours.

3. The nickel-intercalated niobium disulfide according to claim 2, characterized in that, The particle size of metallic nickel, metallic niobium, and elemental sulfur in step 1 is 3-300 μm.

4. The nickel-intercalated niobium disulfide according to claim 2 or 3, characterized in that, The uniform grinding in step 1 is low-temperature grinding, with a grinding temperature below 60°C.

5. The nickel-intercalated niobium disulfide according to claim 1, characterized in that, In step 2, the assembly process of the billet in the high-pressure synthesis assembly is as follows: a dolomite ring is placed in the central hole of the pyrophyllite synthesis block as an insulation layer, and an alumina ceramic tube and a magnesium oxide liner are sequentially inserted into the hole to form an insulation and shaping structure; then a graphite tube is placed as a heating element, and graphite sheets are placed at both ends to form a uniform heating field; next, the sample is encapsulated in a BN sample chamber, and molybdenum sheets and steel sheets are sequentially assembled outside the chamber, and the whole assembly is placed in the center of the magnesium oxide liner; a thermocouple is led out from the sample chamber for temperature monitoring; steel caps are installed at both ends of the synthesis block as electrodes and pressure transmission components, thus completing the preparation of the high-pressure synthesis assembly.